Effects of the Interfacial Bonding Behavior on the Mechanical Properties of E-Glass Fiber/Nanographite Reinforced Hybrid Composites. (18th November 2021) - Saravanan, N.; Yamunadevi, V.; Mohanavel, V.; Chinnaiyan, V. Kumar; Bharani, Murugesan; Ganeshan, P.; Raja, K.; Karthick, Alagar
Abstract : The nanoparticles are incorporated into the composite to mark their unique properties. This work investigates the hybrid epoxy nanocomposite and the impact of nanographite reinforcement. The composite was prepared by using a mechanical stirring technique. The amount of nanographite was added in different volumes, i.e., 1.0, 1.5, and 2.0 wt.%. Results of mechanical and dynamic loading properties were analyzed in accordance to the quantity of nano-G. The fiber and matrix interfacial bonding enrichments were evident in high-resolution SEM images-tensile fracture surface. Finally, the optimum content of nanoparticle which impacts the sample greatly was found to be 1.5 wt.%.